Bone micro-architecture, estimated bone strength, and muscle strength in elite female athletes: a HR-pQCT study - Schipilow, J.; Liphardt, A. M.; Kan, M.; Buie, H.; Macdonald, H.; Boyd, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Athletes participating in sports characterized by specific loading modalities show different levels of bone adaptation [1]. It is unclear how these loading environments affect bone macro- and micro-architecture and estimated bone strength, all contributors to bone quality. Furthermore, the relative role of impact versus muscle forces in determining bone quality remains a topic of debate [2]. The purpose of this study was to (1) investigate the differences in bone macro- and micro-architecture and estimated bone strength in elite female athletes; and (2) gain further insight into the muscle-bone relationship. Methods: Elite female athletes (N=54) participating in high-impact (alpine skiing, n=10), moderate-impact (soccer, n=11), and non-impact sports (swimming, n=11), and 9 controls were measured at the dominant distal tibia using high-resolution peripheral quantitative computed tomography (HR-pQCT). Outcomes included total volumetric bone mineral density (vBMD), total area (Tt.Ar), and cortical area (Ct.Ar). Finite element analysis was used to estimate failure load (FL) of the bone. Muscle strength was assessed by measuring isokinetic knee extension torque (KET) with a Biodex dynamometer. Means were compared using a one-way ANOVA. Pearson correlations were used to identify any relationships between muscle strength and bone parameters. All reported differences and correlations are significant at p<0.05. Results: Swimmers exhibited a vBMD of 281.0 +/- 41.4 mg HA/cm3 (mean +/- SD), which was 19%, 20%, and 15% lower than skiers, soccer players, and controls, respectively. Swimmers displayed a Tt.Ar of 808.1 +/- 122.5 mm2, which was 20% larger than controls; however, swimmer Ct.Ar (109.8 +/- 11.3 mm2) was 17%, 18%, and 14% lower than skiers, soccer players, and controls, respectively. The FL calculated for swimmers (6.0 +/- 0.6 kN) was 24% lower than skiers and 15% lower than soccer players. Skier KET (159.0 +/- 22.0 Nm) was 24% higher than controls. After pooling the data, weak to moderate correlations were found between KET and vBMD (r=0.32), Ct.Ar (r=0.42), and FL (r=0.55). Discussion: Differences in bone parameters are shown between impact and non-impact sports, leading to the inference that impact loading is highly associated with bone quality. The results also show a relationship, albeit a weak to moderate one, between muscle strength and bone parameters. These data suggest that impact loading plays a larger role than muscle strength indetermining bone quality; however, longitudinal prospective studies are required to support this.